Long noncoding RNAs are novel potential prognostic biomarkers for esophageal squamous cell carcinoma: an overview - Deng, Han-Yu; Wang, Yun-Cang; Ni, Peng-Zhi; Lin, Yi-Dan; Chen, Long-Qi (Journal of Thoracic Disease, 2016)
Esophageal squamous cell carcinoma (ESCC) still has a poor prognosis. The prognostic biomarkers of ESCC are not yet well established. Long noncoding RNAs (lncRNAs) have recently been intensively investigated in various cancers including ESCC, and are found to be closely correlated to ESCC. Dysregulated expression of lncRNAs was widely observed in ESCC tumor tissue and was closely related to the tumorigenesis and progression of ESCC. More and more studies have found that lncRNAs were significantly correlated with the prognosis and diagnosis of patients with ESCC. Therefore, all those accumulating evidence indicated that lncRNAs could serve as a prognostic biomarker of ESCC. In this, we summarized the relation between lncRNAs and ESCC as well as the potential biomarker role of lncRNAs in ESCC, especially the prognostic value of lncRNAs. Our current review highlighted the need of further studies to explore the biomarker functions as well as therapeutic values of lncRNAs in ESCC.